Educational System to Approach Teaching of Bi-static Noise Radar - Alejos, A. V.; Garcia Sanchez, M.; Cuiñas, I.; Dawood, M.; R. Mohammed, H. U. (Elektronika ir Elektrotechnika, 2010)
In this paper an experimental radar system is introduced as an aid in teaching an introductory radar system course. The developed radar system is an automated bi-static radar system that has adjustable general features, including the use of pulsed or continuous wave (CW) transmissions, and both coded and uncoded sequences. Additionally, the system is implemented using off-the-shelf low cost components, general purpose laboratory instrumentation, and easy to use software program. We have designated the system with the acronym AmBaR (AutoMated Bi-stAtic Radar). This tool is also used to facilitate the accomplishment of Master Thesis projects with an excellent degree of success. The Problem Based Learning methodology was selected to apply this system in the lab classes. It is intended to be used as a preliminary stage leading to elaborate the adequate and high-quality course guidance/plan. An evaluation methodology is also proposed to measure the the satisfaction level and the effective cognitive learning.